Growth of nanostructured ZnTe thin films through annealing of the MSELD-prepared stack of precursors for photonic applications - Dimple Singh; Naresh Padha; Zakir Hussain; Zahoor Ahmed; Padma Dolma (Chemical Physics Impact)
ZnTe thin films were developed by annealing a stack of precursors deposited using the multisource sequentially evaporated layer deposition method. The deposition was carried out via thermal evaporation in a vacuum of 2 × 10–4 Pa. Annealing was performed at temperatures ranging from 373 K to 573 K under a vacuum of 1 × 10–1 Pa. Structural studies of the as-deposited stack and the films grown on annealing were conducted using X-ray diffraction (XRD). At lower temperatures (373 K and 473 K), the samples exhibited a mixture of ZnTe, Zn, and Te phases. However, at 573 K, a single phase of ZnTe was observed, providing a most significant (111) peak and an impurity peak corresponding to zinc at (002). The ZnTe phase exhibited a cubic crystal structure with a space group of F43 m [213], having a unit cell parameter of a = 6.129 Å and a cell volume of 230 Å3. The Raman spectra of the films grown at 573 K showed peaks at wave numbers of 206, 410, and 616 cm-1, which are attributed to the first, second, and third orders of longitudinal optical (LO) phonon scattering in the ZnTe phase, thus, indicating improved crystallinity of the thin films at this temperature. The direct bandgap values of the films range from 0.67 eV to 1.24 eV at annealing temperatures from 373 to 573 K. Additionally, these films demonstrate a strong absorption coefficient (α) in the range of 2.6 × 10⁴ - 2 × 10⁵ cm⁻¹. These layers displayed a single-phase ZnTe nanostructure with a resistivity of 0.381 Ω·cm and a mobility of 34.7 cm²/V·s, making them suitable for use as an absorber layer in solar cell structures. Consequently, the ZnTe thin films offered potential applications in various photonic devices and served as a viable alternative for absorber layers in solar cell structures.